The Contribution of Digital Literacy to Students' Social Character in PAI Learning: Kontribusi Literasi Digital terhadap Karakter Sosial Siswa dalam Pembelajaran PAI - Sabri, Yasirwan Agis; Junaidi , Junaidi; Samsudin, Muhammad Aso (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the digital era of Society 5.0, information technology profoundly influences education, demanding digital literacy as a foundational competence. Specific Background: Despite this shift, its role in shaping students’ social character—especially within Islamic Religious Education (PAI)—remains underexplored. Knowledge Gap: Previous studies seldom quantify the relationship between digital literacy and specific social character traits such as empathy, cooperation, and tolerance in a religious education context. Aims: This study investigates the influence of digital literacy on the formation of students' social character in PAI learning. Results: Using a quantitative correlational approach involving 80 randomly selected 11th-grade students from SMAN 1 Jonggat, simple linear regression revealed a significant effect (p = 0.001) of digital literacy on social character, with a 24.3% contribution. Novelty: This study offers a rare empirical measurement of digital literacy’s impact on social character in Islamic education, combining pedagogical, technological, and moral dimensions. Implications: The findings support the integration of digital literacy in PAI through TPACK-based teacher training, positioning digital tools not only for content delivery but as instruments for instilling pro-social values. This model may inform national policy and school programs aimed at holistic character education in digital contexts.Highlight : The study found a significant relationship between digital literacy and students’ social character (24.3% contribution). Digital tools in PAI learning foster prosocial values like empathy, collaboration, and responsibility. Teachers need TPACK-based training to integrate digital literacy effectively into character education. Keywords : Digital Literacy, Social Character, PAI Learning, High School Students, Character Education